The Female Dimension in the novel "Perempuan Berkalung Turban" by Abidah El Khalieqy: A Study of Feminist Literary Theory - Dina Gasong; Berthin Simega (Journal of World Science, 2024)
This research aims to describe the dimensions of women in the family aspect depicted in the novel "Perempuan Berkalung Turban" by Abidah El Khalieqy, using a feminist literary theory approach. The research method used is qualitative research, in which the data is analyzed descriptively based on the theory of Feminist Literature. The research results from the novel Perempuan Berkalung Turban illustrate that Mrs. Annisa is a wise person, a mother who loves her child, Nisa, who never gives up on learning to ride a horse. Nisa is a good woman. Nisa is a woman who likes to help. Nisa is a woman who loves her Lek. Nisa is an intelligent person. Nisa is a strong woman and an excellent mother to her child. Nisa is a patient woman. Nisa is a tough woman, and even though Samsudin treats her harshly, she remains patient and steadfast. Nisa is a woman with a soft heart. The implication of this research is to show that women's dimensions in the family aspect include social roles involving maturity, the role of wife, and the role of housewife. This opens up insight into the importance of more profound recognition and understanding of the roles and contributions of women in the family structure and society at large.